Population genomics of jaguars (Panthera onca) : comparative assessment of diversity on different genomic and spatio-temporal scales - Piña, Gustavo Pablo Lorenzana (2019)
The jaguar is the largest predator in the Neotropics and an iconic species in many Native American cultures. It is the only extant representative of genus Panthera in the western hemisphere, and is the target of considerable attention from the scientific and conservation communities, given its threatened status across its continental range. Due to habitat loss and direct human persecution, it has already lost over half of its historical range, and some of its remaining populations are isolated and critically endangered. The jaguar has been the focus of several genetic studies and was the first large Neotropical mammal to have its genome sequenced. However, many outstanding questions remain regarding its genetic diversity, population structure and evolutionary history. For example, no genetic study has investigated diversity or structure of jaguar populations across the Amazon region, a major stronghold for the species and an important baseline against which other biomes can be compared. In addition, as jaguar genetic studies transition to genome-wide approaches, an important issue is to assess the performance of different methods, such as alternative strategies to generate and sequence reduced-representation libraries. Such comparisons are still rare in the literature, and jaguar datasets offer a useful opportunity for such an assessment. Finally, as the Jaguar Genome Project moves forward and begins to include population genomic studies, it is relevant to assess the potential of whole genome sequences generated from multiple individuals to investigate the historical demography of different populations, and their power to inform conservation efforts on behalf of this species. This dissertation addresses these three topics, each of which constitutes the focus of a scientific manuscript. In the first study, I employed 11 microsatellite loci to characterize the genetic variability and population structure of Amazonian jaguars, and then performed integrated analyses incorporating previously published data for the same markers collected in the Atlantic Forest and Pantanal biomes. All indices of genetic diversity were consistently higher for the Amazonian population. No genetic subdivision was detected in the Amazon, indicating large-scale connectivity across a sampled area spanning more than three thousand kilometers. We observed that the Atlantic Forest as a whole still retains considerable levels of genetic diversity, but this is currently partitioned among fragments which are increasingly isolated and subjected to heavy anthropic disturbance. The second study reports the collection of genotyping-by-sequencing (GBS) data from 20 wild jaguars representing five different biomes, and for which whole-exome sequencing (WES) data had already been collected by our group. We performed multiple analyses of both genome-wide datasets, estimating genetic diversity and population differentiation indices, and assessing the impact of different parameter settings on these comparisons. We observed that changes in parametrization led to measurable differences in summary statistics for each jaguar population, both between approaches and among distinct analytical batches within each approach, especially for GBS. Diversity was consistently higher for the Amazonian and Pantanal populations, with the Caatinga exhibiting the lowest diversity and highest differentiation from other regions. Our results show that some parameters do influence estimates of diversity and differentiation in ways that may not be fully predictable, highlighting the importance of careful fine-tuning of parameters for obtaining robust and unbiased genomic diversity estimates. The third manuscript describes the generation of eight novel complete jaguar genomes, and their analyses jointly with three other genomes representing different geographic regions. These 11 genomes were analyzed using the pairwise sequentially Markovian (PSMC) method, and also characterized in terms of their runs of homozygosity (ROH) content to investigate more recent phases of their demographic history. Our PSMC results were very consistent among individuals, and indicated that jaguar populations have undergone pronounced cycles of demographic fluctuations in the last 1-2 million years. In addition, the Arizona individual stood out in showing a steeper decline in the last 30,000 years, likely as a result of a recent history of founder events at the edge of the species’ range. As for the ROH analyses, we found a relatively modest burden of homozygosity across most jaguar populations. However, representatives from the Arizona and Atlantic Forest populations showed signals of recent bottlenecks and, in the latter case, inbreeding. These results demonstrate the potential of genome-wide datasets to investigate jaguar demographic history in unprecedented detail, and open up new avenues for conservation genetic efforts targeting this species. Overall, the three studies contained in this dissertation illustrate the use of different types of markers (from traditional microsatellites to whole-genome sequences) and analyses targeting different spatial and temporal scales, to characterize the evolutionary history of a flagship carnivore. Hopefully these studies will contribute to enhance our understanding of jaguar biology and evolution, and provide useful information to be incorporated into conservation efforts on its behalf.